INDEPENDENSI KEJAKSAAN DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA TELAAH KRITIS TERHADAP UNDANG-UNDANG NOMOR 16 TAHUN 2004 TENTANG KEJAKSAAN REPUBLIK INDONESIA - Dedi Sahputra; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Speaking about the state of law then the consequences of all activities required to lean administration and based on the rule of law. One of the important principles of rule of law is the guarantee of the implementation of independent judicial power, free from the influence of other powers to organize judiciary to enforce the law and justice. In the Constitution of the Republic of Indonesia Year 1945 before the change and after the change are not set explicitly (explicit) about the presence of the Prosecutor of the Republic of Indonesia, but only implied (implicit) in Article 24 paragraph 3 provides that: "Other agencies whose functions related the judicial authority regulated by law ". Law No. 16 of 2004 on the Prosecutor of the Republic of Indonesia in Article 2, paragraph 1 states that: "Prosecutor of the Republic of Indonesia, hereinafter in this Act referred to the prosecutor's office is a government agency implementing state power in the field of prosecution and other authorities under the Act" , Law No. 16 of 2004 in Article 19 paragraph 2 that "The Attorney General is appointed and dismissed by the President". Looking at the above settings can be said that the position of the Prosecutor as a government agency that does the State authorities in the field of prosecution, when viewed from the position, meaning that the Prosecutor is an institution under the authority of the executive. Meanwhile, if viewed from the side of the Prosecutor in the prosecution authority means the Attorney running the judiciary. This is where the ambivalence of the position of Attorney Rebublik happened Indonesia in law enforcement in Indonesia.This study is a normative research is a study of the principles of law and the systematics of the law relating to the independence of the prosecutor in the state system of Indonesia critical examination of the Law No. 16 of 2004 on the Prosecutor of the Republic of Indonesia, while the purpose of the study presented was to figure out how independence kejakaan in the law enforcement system under Act No. 16 of 2004 on the Prosecutor of the Republic of Indonesia.From this study showed that at this point, there are problems which are anomalies when faced with the reality that in many countries that the helm of the Prosecutor, the Attorney General, is part of the cabinet (executive) led by the head of government. On the one hand, the Attorney General as law enforcement is required to work to uphold the values of professionalism and is subject to the normative rules of law, but on the other hand the Attorney General is an office of a political nature because the appointment is the prerogative of the head of government.Keywords: Independence of the Attorney-notch-Authority.